The role of disability and depressive symptoms in the relation between objective cognitive performance and subjective cognitive decline - Pacifico, Deborah; Sabatini, Serena; Fiordelli, Maddalena; Albanese, Emiliano (Frontiers in Psychiatry, 2022)
Background: Subjective cognitive decline (SCD) and subjective memory decline (SMD) are common among older people. Evidence linking SCD and SMD with cognitive and memory impairment is inconsistent. Moreover, little is known about the associations of SCD and SMD with disability. We aimed to explore the associations of SCD and SMD with objective cognitive and memory performance, disability, and depressive symptoms. Methods: In a cross-sectional study we conducted face to face interviews in a randomized sample of people aged ≥ 65 years living in the Canton of Ticino, southern Switzerland, between May 2021 and April 2022. We measured subjective cognitive decline with the MyCog, a subsection of the Subjective Cognitive Decline Questionnaire (SCD-Q); cognitive functioning with the Community Screening Instrument for Dementia; memory with the CERAD ten-word list learning task; and disability and depressive symptoms with the WHO-DAS 2.0 and the EURO-D scales, respectively. Results: Of the 250 participants 93.6% reported at least one cognitive difficulty, and 40.0% SMD. Both SCD and SMD were associated with poorer objective cognitive/memory performance, and independently with greater disability, and more depressive symptoms. But in participants with high disability and depressive symptoms subjective and objective cognition were no longer associated. Disability fully mediated the associations of poorer objective cognitive and memory performance with subjective cognitive and memory decline. Conclusions: Routine clinical assessments of cognitive function should include formal enquires about SCD and SMD, and also account for disability and depressive symptoms.